Quality of accounting and tax information in Brazil - Silva, Maysa Alves Correa; Soares, Cíntia Siqueira Araújo; Barbosa Neto, João Estevão (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Analyze the economic, political, and technological factors influencing the production of accounting and tax information in municipalities. Methodology: Data were collected from the 200 largest Brazilian municipalities. Multiple linear regression was performed with the accounting and tax information quality index as the outcome variable. The explanatory variables included economic complexity, tax dependence, manager qualifications, employee qualifications, transparency, and internet access. Results: The results demonstrated a significant relationship between the variables tax dependence, employee qualifications, and municipal transparency. Contributions of the Study: The study contributes to both national and international literature by demonstrating emerging trends related to accounting and tax information quality. It also highlights the benefits of producing higher-quality accounting and tax statements.